THE ROLE OF SOCIAL MEDIA IN PROMOTING GENDER EQUALITY ISSUES - DAUD, ROSY FEBRIANI; Suryanti, Poppy; LARAS, henny DEWI; Miranda, Zesty (Universitas Sang Bumi Ruwa Jurai, 2024)
Mass media has an important role in influencing people's opinions and behavior. People who are accustomed to using mass media can use this platform as a means to fight for gender equality. Gender is a social concept that includes the norms and valuesattached to a person's gender. The aim of this research is to determine the role of social media in promoting gender equality issues. This research uses a qualitative method with a descriptive approach. A descriptive approach is used to explain the results of the development and concept of social media on gender inequality. The results of this research show that this research shows that social media has the potential to play a role in mobilizing and expanding the gender equality movement in Indonesia, enabling youth, advocacy groups, and other individuals to voice gender issues, mobilize support, and spread the movement's messages.Â Keywords: Roles, Social Media, Gender Equality